Pericytes: Intrinsic Transportation Engineers of the CNS Microcirculation - Eltanahy, Ahmed M.; Koluib, Yara A.; Gonzales, Albert (Frontiers in Physiology, 2021)
Pericytes in the brain are candidate regulators of microcirculatory blood flow because they are strategically positioned along the microvasculature, contain contractile proteins, respond rapidly to neuronal activation, and synchronize microvascular dynamics and neurovascular coupling within the capillary network. Analyses of mice with defects in pericyte generation demonstrate that pericytes are necessary for the formation of the blood-brain barrier, development of the glymphatic system, immune homeostasis, and white matter function. The development, identity, specialization, and progeny of different subtypes of pericytes, however, remain unclear. Pericytes perform brain-wide ‘transportation engineering’ functions in the capillary network, instructing, integrating, and coordinating signals within the cellular communicome in the neurovascular unit to efficiently distribute oxygen and nutrients (‘goods and services’) throughout the microvasculature (‘transportation grid’). In this review, we identify emerging challenges in pericyte biology and shed light on potential pericyte-targeted therapeutic strategies.